CASE STUDY: THE INFLUENCE OF DEEP BREATHING RELAXATION TECHNIQUES IN REDUCING BLOOD PRESSURE AND PAIN CAUSED BY HYPERTENSION: DOI: https://doi.org/10.35654/ijnhs.v1i2.50 - Gusrina Komara Putri; Sri Lestari (Alta Dharma Publisher, 2018)
Pain is a body signal to inform pathological condition. In hypertension patients, pain occurred as one of the symptoms of the disease. Hypertension is an increase if systolic and diastolic blood pressure out of normal range. In Indonesia, especially in Kebayoran Lama public health center district, the prevalence of hypertension in the elderly still consider public health issue. Aim of this study is to measure the effect of deep breath relaxation technique in reducing pain and blood pressure for hypertension patients. This research used a case study design. In this study, a researcher in five days measured participants blood pressures and their pain scales. After that, the researcher guided the participant to do deep breathing relaxation technique five times consecutively, around fifteen minutes. Results pain scale of Mrs. M and Mrs. A that within five days there were slight reducing of pain level. Another finding, that there was a trend of decreasing blood pressure of those patients within the normal range. It can be concluded that in these two patients deep breathing relaxation techniques could reduce their pain scale and maintaining normal blood pressure level of hypertension patients. It is recommended to this research with a bigger sample and using other research variables.